The influence of price and promotion on purchasing decisions at mini market Karya Bersama - Sulini, Sulini; Sinaga, Triana Melinda; Huliman, Huliman (Institute of Computer Science (IOCS), 2024)
This research aims to investigate the influence of price and promotion on purchasing decisions at Mini Market Karya Bersama. The research method uses a quantitative approach by collecting data through surveys of shop customers. The results of the analysis show that price has a positive and significant influence on purchasing decisions (tcount = 4.254, ttable = 1.661, significance = 0.000 < 0.05). This indicates that competitive pricing can increase product attractiveness and support increased sales. Apart from that, promotions also have a positive and significant influence on purchasing decisions (tcount = 3.248, ttable = 1.661, significance = 0.002 < 0.05), indicating that an effective promotional strategy can increase consumer awareness and interest in store products. Simultaneously, price and promotion have a significant influence on purchasing decisions (Fcount = 23.444, Ftable = 3.09, significance = 0.000 < 0.05), with a coefficient of determination (R2) of 0.321, indicating that variations in purchasing decisions 32.1% can be explained by price and promotions. These findings provide practical implications for the management of Mini Market Karya Bersama in designing more effective marketing strategies to increase sales and strengthen their market position